Warming Treatment Methodology Affected the Response of Plant Ecophysiological Traits to Temperature Increases: A Quantitive Meta-Analysis - Wang, Dan; Wang, Hao; Wang, Pengpeng; Ling, Tianqi; Tao, Wenhui; Yang, Zaiqiang (Frontiers in Plant Science, 2019)
Global mean temperature is expected to be significantly higherincreased by the end of the 21st century and could have dramatic impacts on plants growth and physiology and ecosystem processes. Temperature manipulative experiments have been conducted to understand the responsive patterne of plant ecophysiology to climate warming. However, it remains unknown how different methodology conducting used in these experiments will affect plants ecophysiological responses to warming. We conducted a comprehensive meta-analysis of the warming manipulative studies to synthesize the ecophysiological traits responses to warming treatment of different intensities, durations and conducted for different species and under different experimental settings. The results indicated that warming enhanced leaf dark respiration (Rd) and specific leaf area (SLA) but decreased net photosynthetic rate (Anet) and leaf nitrogen content (LN). The positive and negative effects of warming on Rd and Anet were greater for C4 species than C3 species, respectively. The negative effect of warming treatment on Anet and LN and the positive effect on Rd were more evident under > 1 year warming treatment. Negative effects of warming were more evident for plants grown at < 10 L pots when experiment duration was longer than 1 year. The magnitude of warming treatment had a significant impact on most of the parameters that were investigated in the study. Overall, the results showed that warming effects on plant ecophysiological traits varied among different response variables and PFTs, and affected by the magnitude of temperature change and experimental methodology. The results highlight the need for cautiously selecting the values of plant ecophysiological parameters in forecasting ecosystem function changes in future climate regimes and designing controlled experiments to realistically reflecting ecosystems responses to future global warming.